An updated phylogeny, biogeography, and PhyloCode‐based classification of Cornaceae based on three sets of genomic data. Issue 2 (15th February 2023) - Du, Zhi‐Yuan; (Jenny) Xiang, Qiu‐Yun; Cheng, Jin; Zhou, Wenbin; Wang, Qing‐Feng; Soltis, Douglas E.; Soltis, Pamela S.
Abstract: Premise: A major goal of systematic biology is to uncover the evolutionary history of organisms and translate that knowledge into stable classification systems. Here, we integrate three sets of genome‐wide data to resolve phylogenetic relationships in Cornaceae (containing only Cornus s.l.), reconstruct the biogeographic history of the clade, and provide a revised classification using the PhyloCode to stabilize names for this taxonomically controversial group. Methods: We conducted phylogenetic analyses using 312 single‐copy nuclear genes and 70 plastid genes from Angiosperms353 Hyb‐Seq, plus numerous loci from RAD‐Seq. We integrated fossils using morphological data and produced a dated phylogeny for biogeographical analysis. Results: A well‐resolved, strongly supported, comprehensive phylogeny was obtained. Biogeographic analyses support an origin and rapid diversification of Cornus into four morphologically distinct major clades in the Northern Hemisphere (with an eastern Asian ancestor) during the late Cretaceous. Dispersal into Africa from eastern Asia likely occurred along the Tethys Seaway during the Paleogene, whereas dispersal into South America likely occurred during the Neogene. Diversification within the northern hemisphere likely involved repeated independent colonization of new areas during the Paleogene and Neogene along the Bering Land Bridge, the North Atlantic Land Bridge, and the Tethys Seaway. Thirteen strongly supported clades were named following rules of the PhyloCode. Conclusions: Our study provides an example of integrating genomic and morphological data to produce a robust, explicit species phylogeny that includes fossil taxa, which we translate into an updated classification scheme using the PhyloCode to stabilize names.